2007
DOI: 10.1007/s12094-007-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functional status, symptoms and comorbidity in elderly patients with advanced non-small-cell lung cancer (NSCLC) treated with gemcitabine and vinorelbine

Abstract: This biweekly combination is feasible in elderly lung cancer patients with a high burden of comorbidity and dependence. Toxicity is acceptable, whereas response rate and survival fall in the range of active regimens. ADL and IADL indices allow the identification of elderly patients with a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Previously, Maestu et al related functional status and comorbidity in elderly lung cancer patients who were undergoing treatment. 27 The current study revealed that eight CGA domains were prognostic for overall survival (OS) in this group of elderly lung cancer patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previously, Maestu et al related functional status and comorbidity in elderly lung cancer patients who were undergoing treatment. 27 The current study revealed that eight CGA domains were prognostic for overall survival (OS) in this group of elderly lung cancer patients.…”
Section: Discussionmentioning
confidence: 79%
“…Maestu et al also demonstrated a trend toward improved survival in patients without IADL dependency. 27 ADL and IADL may be prognostic and predictive factors in geriatric oncology, but this relationship requires further investigation. 8 Comorbidity is another important CGA domain which is associated with poorer survival in elderly lung cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in keeping with these data, with a non significant tendency for mobility and nutritional status to be associated with OS. We found only one small, open phase II study of 59 untreated patients over 70 years of age with advanced NSCLC showing that ADL and IADL were significantly related to OS in multivariate analysis (24).…”
Section: Discussionmentioning
confidence: 86%
“…As in other advanced cancers (21,22), the number of co-morbidities is also significantly associated with OS in advanced-stage NSCLC. The link between co-morbidities and OS is more readily found in homogeneous elderly NSCLC populations (23)(24)(25). A joint analysis of two prospective randomized trials of systemic chemotherapy (adjuvant/palliative setting) in a total of 1,255 patients with NSCLC showed a clear association between the Charlson comorbidity index and OS (14).…”
Section: Discussionmentioning
confidence: 99%
“…40 Maestu et al presented that comorbidities evaluated by Charlson and Kaplan Feinstein scales were not associated with survival in patients with advanced NSCLC older than 70 years. 41 The possible reason for the lack of prognostic impact in the elderly patient was that these comorbidity scoring systems were not originally designed for the elderly, a population characterized by multiple comorbidities. The comorbidity items and weighing might need to be adjusted in different age groups and disease stages.…”
Section: Discussionmentioning
confidence: 99%